Policy Implementation of Stunting Prevention in Sidokerto Village: Pelaksanaan Kebijakan Pencegahan Stunting di Desa Sidokerto - Mulyaningsih, Dwi; Mursyidah, Lailu (Indonesian Journal of Public Policy Review, 2024)
Background: Stunting remains a major nutritional problem in Indonesia, particularly at the village level where implementation of national policies varies in effectiveness. Specific Background: Sidokerto Village in Sidoarjo is among the prioritized areas for stunting reduction programs. Knowledge Gap: Limited studies have examined how local governments apply national stunting policies through village-based health systems. Aim: This study analyzes the implementation of the stunting prevention program in Sidokerto Village using Edward III’s policy implementation theory. Results: The findings reveal effective communication and community engagement but limited resources, delayed fund disbursement, and insufficient training. Novelty: This research integrates psychosocial approaches with administrative perspectives to assess village-level health policy implementation. Implications: Strengthening local resource management, continuous cadre training, and bureaucratic efficiency are essential for sustainable stunting prevention in rural communities. Highlights:• Integration of psychological and administrative approaches• Village-based implementation of national stunting policy• Community participation and resource constraints Keywords: Stunting, Policy Implementation, Village Health, Public Administration, Prevention